The evolution of secularization theory: from monopoly to crisis - K.I. Shvalagina (Українське Pелігієзнавство, 2008)
Secularization theory is one of those intellectual products that determine the understanding of religion, its status in society, and the changes that take place between faith and unbelief, between church and state, for quite some time. Constituted in the United States in the mid-twentieth century, this theory has found many followers both in America and in Europe, even in the USSR. Its validity and integrity, evidentiality and obviousness did not cause any doubt either to scholars or to religious and statesmen. It was clear that society is liberated from the influence of religion and the church, is rapidly secularized, which will inevitably lead to the transformation of religion into a marginal phenomenon, and eventually - to its extinction. But the predictions that were made with unqualified certainty did not come true, as the development of the religious environment at the end of the XX and the beginning of the XXI century showed. Not only has religion not lost its significance for the modern man, but he is also actively returning to the public sphere. In line with such objective changes, secularization theory undergoes significant transformations, evolving from a monopoly that it has had for almost half a century, to a crisis, and eventually to its antipode, a theory of desecularization.